STUDI ANALISIS KONSEP HADHANAH PERSPEKTIF UNDANG-UNDANG NOMOR 23 TAHUN 2002 TENTANG PERLINDUNGAN ANAK - M. Iqbal (FAKULTAS SYARIAH DAN EKONOMI ISLAM IAI ALMUSLIM, 2023)
The purpose of this writing is to analyze hadhanah from the perspective of Law Number 23 of 2002 concerning child protection. There is no law that clearly and firmly regulates the obligations for child custody to be given to the biological mother or biological father after a divorce occurs. In Law Number 23 of 2002 concerning Child Protection, Article 3 states that child protection aims to guarantee the fulfillment of children's rights so that they can live, grow, develop and participate optimally in accordance with human dignity, as well as receive protection from violence. and discrimination, for the sake of realizing Indonesian children who are qualified, have noble character and are prosperous. There are various reasons that may make parents unable or unwilling to provide for their children. There are several common causes or factors that cause parents not to fulfill their obligations to their children, such as economic factors, personal relationships, or other legal problems.